2017
DOI: 10.2147/ndt.s134008
|View full text |Cite
|
Sign up to set email alerts
|

Cost-utility of collaborative care for the treatment of comorbid major depressive disorder in outpatients with chronic physical conditions. A randomized controlled trial in the general hospital setting (CC-DIM)

Abstract: PurposeMajor depressive disorder (MDD) is highly prevalent in patients with a chronic physical condition, and this comorbidity has a negative influence on quality of life, health care costs, self-care, morbidity, and mortality. Research has shown that collaborative care (CC) may be a cost-effective treatment. However, its cost-effectiveness in this patient group has not yet been established. Therefore, the aim of this study was to evaluate the cost-utility of CC for the treatment of comorbid MDD in chronically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…the meta-analyses [24,[36][37][38]. The adapted PRISMA flowchart of the review update is presented in Fig.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…the meta-analyses [24,[36][37][38]. The adapted PRISMA flowchart of the review update is presented in Fig.…”
Section: Search Resultsmentioning
confidence: 99%
“…This contrast in the findings by study design highlights a well-documented trade-off between attributability and practicability [88]. In our review, several observational economic evaluations barely took any measures to mitigate for treatment contamination or selection bias, thereby jeopardizing causal inference [36,52,55,64,68,69,71,74]. Although experimental designs are the gold standard for robust causal inference, their adoption in evaluating integrated care has been criticized due to their rigidness and low generalizability [89,90].…”
Section: Findings and Interpretationmentioning
confidence: 97%
See 1 more Smart Citation
“…Although more procedures make CC more costly, several studies have shown that CC improves quality of life for acceptable additional costs [38,75]. This has been shown to be the case for depression comorbid with various chronic medical conditions [76][77][78][79][80][81].…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Although more procedures make CC more costly, several studies have shown that CC improves quality of life for 14 acceptable additional costs [38,75]. This has been shown to be the case for depression comorbid with various chronic medical conditions [76][77][78][79][80][81].In patients with ACS, comorbid depression is associated with poorer quality of life [82]. Therefore, given that CC has a better effect than CAU on depression, the fact that depression treatment in ACS has a known favourable prognostic effect on cardiac outcomes [83], and the fact that CC has a positive effect on physical outcomes, CC should be considered a good treatment option in ACS.…”
mentioning
confidence: 99%